Joseph Pulitzer papers - Pulitzer, Joseph, 1847-1911.
Chiefly letters and telegrams from Pulitzer to members of his staff including Frank Irving Cobb, John Norris, and Don Carlos Seitz. Includes other correspondence, memoranda, writings by and about Pulitzer, critiques of editorials, biographical material, and other papers. Subjects include political affairs, Theodore Roosevelt's authorization to purchase Panama Canal rights, Nelson W. Aldrich, William Jennings Bryan, George B. Cortelyou, Theodore Roosevelt, Charles Taft, and William H. Taft.
Journalist and U.S. representative from New York. Born Józef Politzer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aldrich, Nelson W. -- 1841-1915.; Bryan, William Jennings, -- 1860-1925.; Cortelyou, George B. -- 1862-1940.; Cobb, Frank Irving, -- 1869-1923 -- Correspondence; Norris, John, 1856-1914 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Seitz, Don Carlos, -- 1862-1935 -- Correspondence; Taft, Charles Phelps, -- 1843-1929.; Taft, William H. -- 1857-1930.; Canals, Interoceanic; Journalism; Panama Canal (Panama); United States -- Politics and government -- 1865-1933.; Journalists; Representatives, U.S. Congress -- New York (State)